Assessing Vision Mission Goals and Objectives (VMGOs) of Islamic Finance and Banking Program Study Trisakti University - Dida Nurhaida; Aji Kusuma Wijaya; Nuraini Chaniago; Qoriatul Qolbiyyah; Ai Kartini (International Journal of Educational Management and Innovation, 2023)
Every higher educational institution has a vision and mission that reflects its goals, identity, core values, and its purpose of existence. This study aims to assess the clarity, realism, and congruency of the vision mission as well as goals and objectives (VMGOs) of the Diploma Study Program in Islamic Finance and Islamic (IFB) Faculty of Economics and Business, Trisakti University of T and understanding, accepted and carried out by all stakeholders. It also evaluates stakeholder engagement in achieving the vision and mission through practical educational activities and practices. The data were quantitatively analysed utilizing mean and standard deviation. The result shows that Diploma IFB’s VMGOs are visible and realistic among the academic community, including lecturers, academic staff, and students. Their level of understanding and acceptability is immense. They also believe that the activity is in line with these statements. The research recommends that more efforts be made in disseminating VMGOs to internal and external stakeholders. The activities need to be more focused to make them feel that the teaching and non-teaching activities are all geared toward achieving the VMGOs